Paths to Europe: from Byzantium to the Low Countries - Coulie, Bernard 1959-; Dujardin, Paul (Silvana Editoriale, 2017)
As a result of the exhibition 'Paintings from Siena. Ars Narrandi in Europe's Gothic Age', BOZAREXPO organized a colloquium on the influence of Byzantine iconic art on Flemish painting. In the Christian East, these sacred images were venerated
Summary of a conference organized by BOZAR and The A.G. Leventis Foundation, which took place at the Centre for Fine Arts in Brussels, Belgium on 18 January 2015
Keywords: Geschichte 1100-1500; Kunst; Rezeption; Beziehung; Byzantinisches Reich; Niederlande; Siena; 20.30 history of art: general; Konferenzschrift -- 18.01.2015 -- Brüssel